Perkawinan Yang Dicatatkan Pada Kantor Catatan Sipil Tanpa Melakukan Upacara Keagamaan - A.A Poetri Paraniti (Jurnal Ilmiah Raad Kertha, 2019)
Marriage is one of the important events in human life. Every person orpartner (male and female) if they have married then there is a bond of obligationand rights between them and children born from the marriage. Article 2 paragraph(1) of the marriage law that a marriage carried out according to each religion isthe main principle of a legal marriage. The formulation of the problem in this studyis a. What is the authority of the Desa Adat Institution in Bali in determining themarriage conditions before being registered. b. What are the Terms of MarriageAccording to Customary Law of Bali. that method. by using empirical legalresearch methods, namely legal research conducted because of the gap between theory and reality. In order for marriage to be considered legal as customary, itmust carry out Tri Upa Witness, namely Manusa Witness, Buta Witness, and Godof Witness. And administration must be recorded in the civil registry office.